Diversity and altitudinal structure of darkling beetles (Tenebrionidae) in the Zarafshan Valley, Uzbekistan - MANZURA S. UMIRZOKOVA; ISLAMBEK M. AREPBAEV; DILSHOD N. OLJAYEV; SHOVKAT U. BAYSARIYEV; ULUGBEK N. USANOV; MASHKHURA S. SAFAROVA; RANO S. URAZOVA; MUSLIMBEK A. DAMINOV; GULOM M. SAYFULLAYEV; RAFIK A. KHAMZAEV; MUKHAMMADTUYCHI R. RAKHIMOV; IXTIYOR B. AKRAMOV; LUIZA KH. ALIMOVA; FAZLITDIN Z. KHALIMOV (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Umirzokova MS, Alimova LKH, Akramov IB, Rakhimov MR, Khamzaev RA, Sayfullayev GM, Daminov MA, Urazova RS, Safarova MS, Usanov UN, Baysariyev SU, Oljayev DN, Arepbaev IM, Khalimov FZ. 2026. Diversity and altitudinal structure of darkling beetles (Tenebrionidae) in the Zarafshan Valley, Uzbekistan. Biodiversitas 27 (4): d270411. https://doi.org/10.13057/biodiv/d270411. Darkling beetles (Tenebrionidae) are a major component of arid and semi-arid ecosystems and are widely used as indicators of environmental conditions, particularly under increasing aridization in Central Asia. The present study aims to assess species diversity, taxonomic structure, and altitudinal patterns of Tenebrionidae assemblages in the Zarafshan Valley, one of the most biogeographically heterogeneous regions of Uzbekistan. Sampling was conducted in 2022-2024 across 30 localities representing different elevations and vegetation types. Beetles were collected using pitfall traps, light traps, and manual sampling. Uzbekistan, using standardized sampling across 30 sites (2022-2024). A total of 84 species belonging to 36 genera, 17 tribes, and 4 subfamilies were recorded, including 1 genus newly reported for Central Asia and 11 species newly recorded for Uzbekistan. Community structure was characterized by high diversity (Shannon H′: 3.67; Simpson 1-D: 0.96) and low dominance (D: 0.04), indicating a relatively balanced assemblage. Multivariate analyses revealed significant compositional differentiation along the elevational gradient (PERMANOVA: R²: 0.176, p: 0.009), with a strong association between elevation and community structure in PCA ordination (R²: 0.492, p: 0.002). Overall, the results support a pattern of continuous, gradient-driven restructuring of Tenebrionidae communities rather than sharply defined altitudinal belts. These findings provide a quantitative baseline for monitoring climate-driven changes in arid insect communities and highlight the importance of integrating environmental variables in future studies to clarify the mechanisms underlying elevational patterns.